(3eONd GSJQGJjLj cej JMdjdjs - (3eMehO LGSe(B, (3GdUejOYjs; (3QOjfI YKeGf jhSa(B, s ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2005)
(3GdeaGgje GdCSGSjI ddNOeGJ hCHYGOgG, GdJShjb GdeUQaj, Gdeaghe hGdJWhQ, GdNOeGJ GdeUQajI, fTCI hJWhQ hXGFa GdeUGQa, GdJNWjW GdESJQGJjLj ddJShjb GdeUQaj, GSJQGJjLjGJ GdJShjb GdeUQaj, GdShb GdeUQajI, eONd GdfXe hOhQg aj GdJShjb GdeUQaj, GdefJL GdeUQaj, JSYjQ GdNOeI GdeUQajI, JhRjY GdNOeI GdeUQajI, JQhjL GdNOeI GdeUQajI, JMOjO GdecGfI GdPgfjI ddeUQa hSdhc GdeSJajO ddNOeIs
(3HHdjhZQGajG(B: (3U(B.341s
Keywords: (3GdHfhcs; (3GdJShjbs; (3GdNOeGJ GdJLGQjIs